2007
DOI: 10.1051/vetres:2006052
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of sCD14 by bovine neutrophils following activation with bacterial lipopolysaccharide results in down-regulation of IL-8

Abstract: -CD14, the leukocyte co-receptor for lipopolysaccharide (LPS), is important in the response of bovine polymorphonuclear neutrophil leukocytes (PMN) to Gram-negative bacteria. In other species, the expression of CD14 on the surface of PMN was shown to increase after exposure to inflammatory stimuli. These newly expressed molecules may originate from either an intracellular pool or through new gene expression. We sought to characterize bovine PMN cell surface expression and shedding of CD14 molecules, and CD14's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…A study of respiratory damage in children chronically exposed to urban pollution in Mexico City showed that serum levels of IL-8 were decreased when compared with children living in a cleaner environment [35]. The downregulation of IL-8 has been related to different factors, such as relatively late sampling [36], the presence of IL-4 and IL-10 [37], and soluble receptors of TNF-a or CD14 [38,39]. In the present study, decreases were observed in the IL-8 secretion by A549 cells and by the biculture of A549 + HMC-1, but large increases in IL-8 secretion were observed in the HMC-1 + THP-1 biculture, the triculture and the triculture with EAHY926 at concentrations of 10 and 30 mg?cm -2 PM10, followed by a decrease at 100 mg?cm -2 .…”
Section: Cellular Interactionmentioning
confidence: 99%
“…A study of respiratory damage in children chronically exposed to urban pollution in Mexico City showed that serum levels of IL-8 were decreased when compared with children living in a cleaner environment [35]. The downregulation of IL-8 has been related to different factors, such as relatively late sampling [36], the presence of IL-4 and IL-10 [37], and soluble receptors of TNF-a or CD14 [38,39]. In the present study, decreases were observed in the IL-8 secretion by A549 cells and by the biculture of A549 + HMC-1, but large increases in IL-8 secretion were observed in the HMC-1 + THP-1 biculture, the triculture and the triculture with EAHY926 at concentrations of 10 and 30 mg?cm -2 PM10, followed by a decrease at 100 mg?cm -2 .…”
Section: Cellular Interactionmentioning
confidence: 99%
“…The association of LPS-bound CD14 with Toll-like receptor 4 and the accessory protein MD-2 triggers the eventual production of effector proteins such as IL-8. Sohn et al (29) have demonstrated a correlation between the levels of soluble CD14 and IL-8 production.…”
Section: Discussionmentioning
confidence: 97%
“…In this review we will focus on sCD14 as an APP. The serum sCD14 is believed to originate from enzymatic cleavage of its membrane homologue mCD14 through the action of specific phospholipases or proteases (Bazil et al, 1989, Sohn et al, 2007. It was first described by Maliszewski et al (1985) as a culturesupernatant blocking factor, soluble My 23, an antigen from human myeloid cells that was able to block staining of monocytes by anti-CD14 monoclonal antibodies.…”
Section: Functionsmentioning
confidence: 99%
“…Soluble CD14 also functions as a soluble receptor for bacterial LPS to cells that do not express CD14 such as epithelial and endothelial cells and thereby activates TLR-4 and the release of cytokines (Frey et al, 1992;Kitchens & Thompson, 2005). Toll-like receptor 4 mediates cellular responses to microbial LPS and acts as a co-receptor with mCD14 for LPS (Sohn et al, 2007). Soluble CD14 also has pro-inflammatory activities in the extravascular compartments where it increases resistance to bacteria.…”
Section: Functionsmentioning
confidence: 99%
See 1 more Smart Citation